2020
DOI: 10.3390/ijms21228481
|View full text |Cite
|
Sign up to set email alerts
|

Bone Fracture Enhanced Blood-Brain Barrier Breakdown in the Hippocampus and White Matter Damage of Stroke Mice

Abstract: Background: Tibia fracture (BF) before stroke shortly causes long-term post-stroke memory dysfunction in mice. The mechanism is unclear. We hypothesize that BF enhances neuroinflammation and blood brain barrier (BBB) breakdown in the hippocampus and white matter (WM) damage. Methods: Mice were assigned to groups: BF, stroke, BF+stroke (BF 6 h before stroke) and sham. BBB integrity was analyzed 3 days after the surgeries and WM injury was analyzed 3 days and 8 weeks after the surgeries. Results: Stroke and BF+s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It has been reported that WM damage 42 and ipsilateral hippocampal atrophy is associated with long-term memory dysfunction after ischemic stroke. 43 Our previous studies showed WM 44 and GCL atrophy 9 in mice 8 weeks after BF and stroke. In this study, we showed that inhibition of inflammation through PHA treatment reduced WM and GCL atrophy and increased neurogenesis in DG at the subacute stage of the injuries.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that WM damage 42 and ipsilateral hippocampal atrophy is associated with long-term memory dysfunction after ischemic stroke. 43 Our previous studies showed WM 44 and GCL atrophy 9 in mice 8 weeks after BF and stroke. In this study, we showed that inhibition of inflammation through PHA treatment reduced WM and GCL atrophy and increased neurogenesis in DG at the subacute stage of the injuries.…”
Section: Discussionmentioning
confidence: 92%
“…23,24 Moreover, there was a pronounced blood-brain barrier (BBB) breakdown. 25 Detrimental effects were also seen when bone fracture was induced after pMCAO. 26 Poststroke bone fractures are further associated with larger brain edema volumes in subacute stroke stages, 27 potentially due to mentioned BBB breakdown.…”
Section: Differen Ce S In Pathophys Iolog Ic Al Mechanis Ms In Periop...mentioning
confidence: 99%
“…120 Biomaterials and scaffolds may help to provide such cues in larger lesions, 152 whereas smaller lesions or those predominantly situated in the white matter may be attractive targets for restorative therapies. 25,153 However, a profound preclinical proof of concept of restorative approaches is not available so far, and any clinical application is unlikely to happen in the near future.…”
Section: Restorative Approachesmentioning
confidence: 99%